The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1055/s-0030-1247797
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications After High Tibial Osteotomy –A Comparison of Two Techniques

Abstract: This prospective cohort study compared opening wedge high tibial osteotomy with use of the Puddu plate and the Vitoss synthetic cancellous bone versus closing wedge high tibial osteotomy with use of the AO/ASIF L-plate, focusing on complications (nonunions, infections, loss of correction, reoperations) and patient satisfaction (visual linear analog scale). During a 10-month period, we performed high tibial osteotomy for 40 patients experiencing medial knee osteoarthritis and a varus deformity. The average foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 38 publications
5
59
1
1
Order By: Relevance
“…54 In a randomized study comparing the 2 techniques, at 1 year follow-up, more accurate coronal plane corrections were achieved using a lateral closing wedge technique, compared with a medial opening wedge technique, although at this short-term time point, the clinical outcome scores were not statistically different between patient groups. 7…”
Section: Lateral Closing Wedge Htomentioning
confidence: 89%
See 1 more Smart Citation
“…54 In a randomized study comparing the 2 techniques, at 1 year follow-up, more accurate coronal plane corrections were achieved using a lateral closing wedge technique, compared with a medial opening wedge technique, although at this short-term time point, the clinical outcome scores were not statistically different between patient groups. 7…”
Section: Lateral Closing Wedge Htomentioning
confidence: 89%
“…51,54 Other possible complications described in case reports include compartment syndrome, hematoma, pseudarthrosis of the fibula, complex regional pain syndrome, and failure of osteosynthesis, with or without loss of correction. Exact frequencies are not available in the literature.…”
Section: Complicationsmentioning
confidence: 99%
“…The opening-wedge osteotomy with a Puddu plate was associated with a higher number of complications. In a prospective cohort study by von den Bekerom et al, 15 comparison of a lateral AO/ASIF L-plate (AO, Davos Platz, Switzerland) with a medial Puddu plate showed a higher rate of non-union, loss of correction and failure of the implant in the opening-wedge group. In our study, the results were comparable in terms of range of motion, union, amount of correction and the complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have correlated lateral cortex fractures with instability and development of pseudarthrosis or loss of correction (3,10,11) . Our study found pseudarthrosis in 4.4% and joint stiffness in 6.52%, which correlated directly with the lateral cortex fracture rate and longer duration of postoperative immobilization.…”
Section: Discussionmentioning
confidence: 99%